A few notes on fundamental approaches in the postmodern theories of culture - I. A. Sajtarly, (Ukrainian Cultural Studies, 2018)
This article is devoted to a complicated problem in the postmodern philosophy of culture, within framework of that there is ambiguous attitudes to understanding of cultural field. On the one hand, the postmodern thinkers criticize the traditional culture, which in their opinion is based on repressions and violence. On the other hand, they reject the current system of values because they consider it to be decadent in relation to both humans and society. It should be concluded from this philosophy, that in the role of "schizoid subject", in contrast with postmodernist arguments, we have reached a limit not for capitalism, but mainly for culture.
Keywords: Oedipus complex, unconsciousness, schizoid subject, anthropological type, phantasm, desiring-production